Tribal Youth, Public Sphere and Higher Education in Tripura - Dubey, Rajeev (JOURNAL OF INDIAN EDUCATION, 2020)
This paper deals with the crisis of higher education in general and Tripura in particular. It seeks to raise the debate from mere economic analysis of the crisis ailing the higher education to the socio-cultural aspects of the crisis. Institutions of higher education are ideally poised to nurture public sphere in the educational space. Our constitution makers realised that the marginalised group of society needs to be adequately represented in HEIs, as this representation beside other benefits would also provide them a platform to air their views, opinion and interest in the discourses taking place in public sphere which play a pivotal role in shaping the contours of public policy. This paper attempts to provide a critical and reflexive glance at the participation of tribal youth in current mainstream higher educational institutions (HEIs) in general and Tripura in particular. Through data procured from secondary sources, researcher seeks to establish that through various means of social closure in the institutions of higher education, the representation and participation of tribal youth is far from the constitutional mandate. The hidden curriculum and banking pedagogy further aid and facilitate the process of marginalisation of tribal youth. This lack of representation of tribal youth significantly undermines their participation in public sphere of HEIs, which eventually plays an important role in shaping the contours of public policy.